Evaluating citrus juice: A comparative study of physicochemical, nutraceutical, antioxidant, and antimicrobial properties of citrus juices from Nepal - Nirmal Karki; Hari Achhami; Bishwa Bandhu Pachhai; Susmita Bhattarai; Dikpal Kumar Shahi; Lok Ranjan Bhatt; Mahesh Kumar Joshi (Heliyon)
Citrus fruit juice is highly beneficial to human health, providing essential nutrients like carbohydrates, vitamins, phytochemicals, and antioxidants. Juices from citrus fruit varieties grown in various regions of Nepal were analyzed for their physicochemical properties, nutraceutical content, antioxidant and antimicrobial properties. The pH of the juices ranged between 2.09 and 3.62, while total soluble solids (TSS) varied from 7° Brix to 12.3 °Brix. Among varieties, C. aurantifolia exhibited the highest titratable acidity at 7.39 g/100 mL. C. limon showed the highest moisture content (94.74 %), C. reticulata had the highest carbohydrate content (14.6 ± 0.4 g/100 mL, n = 3), and C. aurantifolia presented the highest protein content (34.1 ± 0.7 mg/100 mL). C. sinensis recorded the highest flavonoid content (91.4 ± 0.3 mg/100 mL), C. reticulata had the highest phenolic content (65.8 ± 0.6 mg/100 mL), and C. limon exhibited the highest ascorbic acid content (45.1 ± 0.4 mg/100 mL). The methanolic extracts of all citrus fruit juices demonstrated robust antioxidant properties, as determined by DPPH assay. Notably, C. limon and C. aurantifolia juice extracts demonstrated significant antimicrobial activity against a wide range of microbes. This study highlights the variation in nutrient and phytochemicals compositions among different citrus fruit juices, underscoring the nutritional and medicinal benefits of citrus species.